2017
DOI: 10.1509/jppm.16.108
|View full text |Cite
|
Sign up to set email alerts
|

U.S. Citizens’ Representations of God and Support for Sustainability Policies

Abstract: This study proposes that certain religious and spiritual beliefs—specifically, representations of God—play an indirect but influential role in cognitive processing of (1) sustainability behaviors, (2) the importance of proenvironmental policies, and (3) their willingness to vote for proenvironmental policies. Across three studies, this research investigates the role of three representations of God: (1) God as an authoritarian personified being, (2) God as a benevolent personified being, and (3) God as a mystic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 68 publications
3
42
1
Order By: Relevance
“…Notably, however, the reverse may also be true: Self-transcendent feelings elicited by awe experiences may lead to greater feelings of connectedness. Consistent with this reasoning, prior research has shown that awe experiences (e.g., seeing the earth from space) promote feelings of connectedness via self-transcendence [18, 19]; that is, awe experiences bring about feelings of awe and other self-transcendent emotions, which in turn promote greater feelings of connectedness.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…Notably, however, the reverse may also be true: Self-transcendent feelings elicited by awe experiences may lead to greater feelings of connectedness. Consistent with this reasoning, prior research has shown that awe experiences (e.g., seeing the earth from space) promote feelings of connectedness via self-transcendence [18, 19]; that is, awe experiences bring about feelings of awe and other self-transcendent emotions, which in turn promote greater feelings of connectedness.…”
Section: Introductionmentioning
confidence: 69%
“…Finally, experiential methodologies provide participants with specific experiences that would evoke awe, such as viewing an expansive T-Rex skeleton [13], viewing the surrounding area from the top of a bell tower [6], or visiting a grove of tall trees [2]. Across induction procedures, images of the universe, planet Earth, stars, or outer space are quite common: 51% of 35 experiments relied on such images to induce feelings of awe [2, 6, 7, 8, 10, 11, 13, 14, 15, 16, 17, 18, 19].…”
Section: Introductionmentioning
confidence: 99%
“…We predict that authoritarian God concept, which tends to correlate positively with conservatism (K. A. Johnson et al, 2017;Thomson & Froese, 2016), would be positively correlated with the binding foundations and that an authoritarian God prime would likewise increase endorsement of the binding foundations. In contrast, we predict that benevolent God concept would be positively correlated with the individualizing foundations and a benevolent God prime would increase endorsement of individualizing foundations.…”
Section: Studymentioning
confidence: 91%
“…Second, religion serves as a primary value system for well over half of consumers worldwide (Pew Research Forum, 2017), and provides a viable market segmentation characteristic given similarities in values among religious individuals (Schmidt et al, 2014). Finally, religion has numerous influences on consumption behavior (Agarwala et al, 2019; Mathras et al, 2016) and is more easily targetable in marketing campaigns using social media advertising selection characteristics (Johnson et al, 2017).…”
Section: Consumers' Sense Of Belonging and Need‐to‐belong Theorymentioning
confidence: 99%
“…An understanding in this area is critical because religion has been argued to influence many consumption decisions (Mathras, Cohen, Mandel, & Mick, 2016). Additionally, religious references can be incorporated into marketing communications, personal sales presentations, and segmentation/target market strategies to improve customer relationships and profits (Agarwala, Mishra, & Singh, 2019; Johnson et al, 2017). With over 80% of consumers worldwide following some sort of religious belief (Hackett & McClendon, 2017), it seems imperative to comprehensively understand how these beliefs and their influence on belongingness drive consumption behavior.…”
Section: Introductionmentioning
confidence: 99%